2020
DOI: 10.1002/cpp.2479
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceived lack of goal clarity in psychological treatments: Scale development and negative correlates

Abstract: Goal setting in psychological treatments may have favourable effects on patients' motivation and treatment outcomes. Therefore, it seems important to detect when patients do not perceive clear treatment goals. The current study presents a questionnaire measuring patients' perceived lack of goal clarity. The cross-sectional study consisted of 742 adult outpatients with diverse mental disorders. Patients completed the perceived lack of goal clarity questionnaire, and additional items measuring goal setting and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For instance, we would hypothesize that patients' agency within the therapy context, as measured by the Therapeutic Agency Inventory (Huber et al, 2019), would be related to and preceded by their observerrated insight (Jennissen et al, 2018), emotional awareness (Høglend and Hagtvet, 2019), and reflective functioning levels (Fonagy and Target, 1996;Fonagy et al, 2016), as well as less frequent use of immature defenses (Perry, 1990). Likewise, we would hypothesize that increases in clients' awareness (Geurtzen et al, 2020) and internalization (Pelletier et al, 1997) of their own therapeutic goals would precede and predict increases in therapeutic gains as well as general self-efficacy (Schwarzer and Jerusalem, 1995)-a measure closely tied to our understanding of physical agency.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For instance, we would hypothesize that patients' agency within the therapy context, as measured by the Therapeutic Agency Inventory (Huber et al, 2019), would be related to and preceded by their observerrated insight (Jennissen et al, 2018), emotional awareness (Høglend and Hagtvet, 2019), and reflective functioning levels (Fonagy and Target, 1996;Fonagy et al, 2016), as well as less frequent use of immature defenses (Perry, 1990). Likewise, we would hypothesize that increases in clients' awareness (Geurtzen et al, 2020) and internalization (Pelletier et al, 1997) of their own therapeutic goals would precede and predict increases in therapeutic gains as well as general self-efficacy (Schwarzer and Jerusalem, 1995)-a measure closely tied to our understanding of physical agency.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Lack of structure, perhaps evidenced by a lower number of chat sessions, could explain why less progress is made towards self-set goals. Indeed, making explicit, collaborative goals, and discussing these regularly, is associated with lower levels of negative mental health symptoms in therapy (Geurtzen et al, 2020). Much work may be needed to ensure that digital therapeutic platforms promote structure around self-set, as well as collaboratively set, goals.…”
Section: Service Engagementmentioning
confidence: 99%
“…Setting and monitoring goals within therapy can enhance service‐user motivation, and increase the likelihood of favourable therapeutic outcomes (Geurtzen et al, 2020). Tangible “goals” within psychology were defined by Austin and Vancouver (1996) as “internal representations of desired states” (p. 338), with goal‐focused therapy centred on the devising of clear objectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a widespread acceptance that goals assist therapeutic processes, the research agenda has turned more recently to the way in which goal setting can best be managed. For example, the clarity of the goals set is regarded as important, with Geurtzen et al (2020) reporting that clients who said that their goals were unclear found the therapeutic alliance to be reduced, they reported their symptom levels to be higher, and had a greater need for future sessions. The process used to define goals is also seen as significant, with a collaborative approach being preferred: In their meta-analysis of studies of goal consensus and collaboration across therapeutic orientations, Tryon et al (2018) concluded that when therapists and their clients agree on psychotherapy goals and actively collaborate, they tend to have more positive treatment outcomes.…”
mentioning
confidence: 99%